2011
DOI: 10.1128/jb.06370-11
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the N-Acetylglucosamine Metabolic Genes of Streptomyces coelicolor and Role in Control of Development and Antibiotic Production

Abstract: N-Acetylglucosamine, the monomer of chitin, is a favored carbon and nitrogen source for streptomycetes. Its intracellular catabolism requires the combined actions of the N-acetylglucosamine-6-phosphate (GlcNAc-6P) deacetylase NagA and the glucosamine-6-phosphate (GlcN-6P) deaminase/isomerase NagB. GlcNAc acts as a signaling molecule in the DasR-mediated nutrient sensing system, activating development and antibiotic production under poor growth conditions (famine) and blocking these processes under rich conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 49 publications
0
103
0
Order By: Relevance
“…GlcNAc-derived GlcN-6-P acts as an allosteric effector of the GntR family regulator DasR (186), a global regulator that controls the GlcNAc regulon (186,360,361), and also the production of antibiotics (187) and siderophores (362). GlcNAc-dependent nutritional signaling is most likely mediated through changes in the intracellular level of GlcN-6-P, which binds as a ligand to the GntR family regulator DasR, leading to derepression of DasR-mediated control of antibiotic production (187).…”
Section: Correlation Between Growth and Antibiotic Productionmentioning
confidence: 99%
“…GlcNAc-derived GlcN-6-P acts as an allosteric effector of the GntR family regulator DasR (186), a global regulator that controls the GlcNAc regulon (186,360,361), and also the production of antibiotics (187) and siderophores (362). GlcNAc-dependent nutritional signaling is most likely mediated through changes in the intracellular level of GlcN-6-P, which binds as a ligand to the GntR family regulator DasR, leading to derepression of DasR-mediated control of antibiotic production (187).…”
Section: Correlation Between Growth and Antibiotic Productionmentioning
confidence: 99%
“…The first indirect evidence of a role of GlcNAc-6P in the GlcNAc-mediated response was provided by the examination of the phenotype of the S. coelicolor nagA null mutant (DnagA IFD (GAM4), [23,24]) in which GlcNAc-6P accumulates inside the cytoplasm. As described previously [2], GlcNAc blocks morphological differentiation (sporulation) and antibiotic production of the parental strain S. coelicolor M145 grown on rich R2YE agar plates (see also strains M145 and ET001 in Fig.…”
Section: Intracellular Accumulation Of Glcnac-6p Enhances the Activitmentioning
confidence: 99%
“…DasR-6His was produced in E. coli BL21(DE3) and purified onto a Ni 2þ -nitrilotriacetic acid-agarose column as previously described [23]. Pooled fractions with the pure protein were dialyzed overnight at 4 C against EMSA buffer (10 mM Tris-Cl, pH 7.5, 1 mM dithiothreitol, 0.25 mM CaCl 2 , 0.5 mM MgCl 2 , 50 mM KCl, and 2% glycerol).…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of ubiquist molecules in signalisation has been poorly investigated, several studies confirmed that these molecules are likely to signal specific metabolic state and thus also play important regulatory roles (Viollier et al 2001a, b;Li et al 2008;Rigali et al 2008;Luti and Mavituna 2011). For instance, we have previously demonstrated that the peptidoglycan aminosugar building block N-acetylglucosamine (GlcNAc) has a different impact on development depending on the nutritional context and its concentration (Rigali et al 2006(Rigali et al , 2008Nothaft et al 2010;Craig et al 2012;Swiatek et al 2012).…”
Section: Discussionmentioning
confidence: 96%